The state of patient experience - Jason Wolf (The Beryl Institute, 2015)
As the patient experience movement continues to flourish, there is greater alignment that experience encompasses all we do in healthcare – not simply a customer encounter, but how we engage people in mind, body and spirit, how we integrate the critical aspects of care from quality to safety to service and how we link the very complexities of our healthcare systems globally to provide for easy journeys for those receiving care. In sharing data from the latest study for The Beryl Institute on patient experience, the trends of this growing movement are seen as positive and a set of clear and defined outcomes driven by a positive patient experience are emerging, representing the impact experience now has as a central focus for healthcare globally. The state of patient experience is strong for regardless of national identity or systemic constraints – the idea itself resonates at the core of our humanity. If we approach it from that light, both in practice and in research, the possibilities for a better healthcare world are truly boundless.